Zephaniah : A Commentary - Sweeney, Marvin A. (Marvin Alan), 1953- (Book collections on Project MUSE., 2003)
Sweeney's keen reading of this small, prophetic book opens new doors for Hebrew Bible research. He situates the reading of Zephaniah in the early sixth century B.C.E. rather than the late seventh century b.c.e. Sweeney's interpretation pays close attention to the often subtle differences between the Masoretic Text, Septuagint, Dead Sea Scrolls, Peshitta, and targums. His methodology includes form criticism, tradition history, and social history.